2022
DOI: 10.3390/polym14153015
|View full text |Cite
|
Sign up to set email alerts
|

Graft Polymerization of Stearyl Methacrylate on PET Track-Etched Membranes for Oil–Water Separation

Abstract: In this article, results of PET track-etched membranes (PET TeMs) hydrophobized by photo-induced graft polymerization of stearyl methacrylate (SM) inside the pores were presented. The effects of monomer concentration, time of irradiation and the nature of the solvent on the degree of grafting and membrane morphology were investigated. The PET TeMs with pore diameters ranging from 350 nm (pore density of 1 × 108 pore/cm2) to 3.05 µm (pore density of 1 × 106 pore/cm2) were hydrophobized and tested for oil–water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…The separation of water-oil mixtures with modified PET TeMs was carried out by filtration according to the scheme presented in our previous works [38,39].…”
Section: Performance Of Modified Membranes In Oil-water Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation of water-oil mixtures with modified PET TeMs was carried out by filtration according to the scheme presented in our previous works [38,39].…”
Section: Performance Of Modified Membranes In Oil-water Separationmentioning
confidence: 99%
“…Previously, we have shown that PET TeMs modified by photoinitiated graft polymerization of stearyl methacrylate [38], as well as by soaking in a trichlorooctylsilane solution [39], performed well in the separation of oil-water emulsion. In this paper, we studied a simpler and more energy efficient method of modifying PET TeMs to obtain a pH-responsive surface by soaking in a (poly)allylamine (PAAm) solution for use in the separation of chloroform/water (pH=2) and hexadecane/water (pH=2) systems in various ratios.…”
Section: Introductionmentioning
confidence: 98%
“…Although various methods such as oatation, 4 coagulation, 5 and extraction 6 have been used for this purpose, there is currently a need for the development of advanced separation methods, which can be achieved via new types of membranes 7,8 and modication methods. [9][10][11] One promising avenue is the application of membrane technology in the separation of emulsions, 2,[12][13][14] which is also reected in our previous works 3,15,16 using modied TeMs based on PET for the separation of water-oil emulsions. TeMs, due to a number of advantages (narrow pore size distribution and precise control of the number of pores per cm 2 ), are gaining interest in separation processes as model membranes.…”
Section: Introductionmentioning
confidence: 99%
“…There are known works using PET material as a matrix for the development of membranes, fabrics, and nanobers for the separation of water-oil emulsions, [19][20][21][22] but there are only several works using PET TeMs for this purpose. 3,15,16 In this context and considering the successful application of PET TeMs in the separation of water-oil emulsions, we continued our work on the fabrication of innovative stimuli-responsive membranes by UV-initiated reversible addition-fragmentation chain transfer (RAFT) copolymerization. 3,15,16,23 RAFT polymerization allows to obtain rstly block copolymers and secondly prevents uncontrolled chain growth, i.e., allows to synthesize polymers with a well-dened and narrow distribution of molecular weights, also called low polydispersity index.…”
Section: Introductionmentioning
confidence: 99%
“…13 Membranes with controllable high roughness, such as nanoporous track-etched membranes (TeMs), are created by bombardment with accelerated heavy ions and subsequent chemical etching, resulting in a nanoporous structure with high aspect ratios and a rough surface. The controllable high roughness of TeMs makes them ideal for creating unclogged and effective nanochannels, which can be utilized for various applications, such as water purication, [14][15][16][17][18][19] drug delivery, 20 sensing [21][22][23] and DNA sequencing, 24 and can work locally at high rates and with high selectivity.…”
Section: Introductionmentioning
confidence: 99%